2019
DOI: 10.1002/jcb.29521
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 is necessary for capacitation and acrosome reaction in guinea pig spermatozoa

Abstract: Actin cytoskeleton remodeling is a critical process for the acquisition of fertilizing capacity by spermatozoa during capacitation. However, the molecular mechanism that regulates this process has not been fully elucidated. In somatic cells, Ras‐related C3 botulinum toxin substrate 1 protein (Rac1) promotes the polymerization of actin by participating in the modeling of two structures: lamellipodia and adhesion complexes linked with the plasma membrane. Rac1 is expressed in mammalian spermatozoa; however, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Another possibility is that other RHO protein, not inhibited by Y-27632, would be related to the actin polymerization between the external plasma and acrosomal membranes, an event required to avoid early AR, and that this sperm process occurs in the usual way (Spungin et al 1995, Hernandez-Gonzalez et al 2000, Breitbart et al 2005. We have recently reported that RAC1 could be related to the formation of this cytoskeleton (Ramirez-Ramirez et al 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Another possibility is that other RHO protein, not inhibited by Y-27632, would be related to the actin polymerization between the external plasma and acrosomal membranes, an event required to avoid early AR, and that this sperm process occurs in the usual way (Spungin et al 1995, Hernandez-Gonzalez et al 2000, Breitbart et al 2005. We have recently reported that RAC1 could be related to the formation of this cytoskeleton (Ramirez-Ramirez et al 2020).…”
Section: Discussionmentioning
confidence: 98%
“…RAS-related C3 botulinum toxin substrate 1 (RAC1) has a small GTPase-binding protein structural domain that binds to small GTPases and is involved in actin cytoskeleton remodeling in the apical region of the acrosome during guinea pig spermatozoa capacitation. The formation of the actin cytoskeleton in the apical region of the acrosome is considered a necessary event for spermatozoa capacitation and acrosome reaction in guinea pigs and is driven by Rac1 [ 36 ]. In this study, we also found that RAC1 is differentially expressed in the acrosome-reacting spermatozoa of E. sinensis , suggesting that RAC1 may also regulate actin cytoskeleton remodeling in E. sinensis spermatozoa through its own specific structural domain and participate in the process of acrosome reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The cytoplasmic tail of β4 integrin is significantly longer than other β integrin subunits and has the ability to be involved in cytoskeletal reorganization. It affects, for example, the Rac1 protein (Ras related C3 botulinum toxin substrate 1 protein) and its activation [67], which plays an important role in capacitation and the acrosome reaction, especially in the remodeling of actin in the apical part of the acrosome [68]. Unlike other integrins, β4 binds not only to actin and tubulin but also to intermediate filaments, such as keratin 5 via its counterpart plectin, which surrounds the sperm nucleus [68].…”
Section: The Role Of Integrins In Membrane Reorganization and Stabilitymentioning
confidence: 99%
“…It affects, for example, the Rac1 protein (Ras related C3 botulinum toxin substrate 1 protein) and its activation [67], which plays an important role in capacitation and the acrosome reaction, especially in the remodeling of actin in the apical part of the acrosome [68]. Unlike other integrins, β4 binds not only to actin and tubulin but also to intermediate filaments, such as keratin 5 via its counterpart plectin, which surrounds the sperm nucleus [68]. This binding ability is due to the structural differences of the cytoplasmic domain of β4 (Figure 3) and may contribute to the mechanical and structural stability of a cell.…”
Section: The Role Of Integrins In Membrane Reorganization and Stabilitymentioning
confidence: 99%